(untitled) (Comprehensive Journal of Science, 2025)
This study addresses the morphemic structure of the verb in the Arabic language, considering it as one of the significant linguistic phenomena that reflect the richness and diversity of the language. The study aims to analyze the verb (an applied study) in terms of its morphemic components (root, pattern, and affixes) and to clarify how these components are formed and their grammatical and morphological functions. The research is based on the descriptive-analytical method and is divided into three sections. The first section deals with the concept of the morpheme in modern linguistic studies. The second section focuses on the analysis of the verb according to classical Arabic scholars. The final section addresses the morphemic structure of the verb in modern linguistics, including the applied aspect of the verb kataba – “to write”). This verb serves as a model for comparison between Arabic and other languages in terms of morphological system and morphemic structure. The motivation for this study is to fill existing research gaps. Despite previous studies on verbs in Arabic, there remains a need for a detailed applied analysis that highlights morphemic aspects through the study of specific examples, such as the verb ،The analysis contributes to a more precise understanding of grammatical and morphological rules, which is useful for teaching Arabic to both native and non-native speakers. Such precision also helps in understanding the interplay of meanings among morphemes. Some morphemes, such as the prefix "أ" (a) or the suffix "ت" (t), can serve multiple functions (tense, person, number), making the differentiation between grammatical and semantic functions a challenge that requires careful analytical scrutiny.